Analysis of Modern Grinding Machines Using Flooring Technology - Ibadovich Yusupov, Khamza; Nazarbaevna Salimova, Iroda (International Journal of Psychosocial Rehabilitation, 2020)
In this article describes mosaic floor covering by the motion of practical use and also machines by technic economic indicators. Develop technical specifications and develop a new self-propelled grinding machine, taking into account the need for faster mass production of self-propelled grinding machines with their strictly known technological and design parameters.